Thermoelectric properties of cold pressed samples of semiconductor (Bi₁₋xSbx)₂Te₃ solid solutions - Martynova, K.V.; Rogacheva, E.I. (Functional Materials, 2018)
The composition dependences of thermoelectric (TE) properties of (Bi₁₋xSbx)₂Te₃ solid solutions (0 < x < 1) produced by cold pressing and subsequent annealing were investigated at room temperature. Samples were prepared from cast polycrystals, obtained by the cooling of melt down to room temperature in evacuated quartz ampoules and subsequent annealing. It was established that cast samples exhibited p-type conductivity in the entire composition range, and an increase in the Sb₂Te₃ content led to the growth of electrical conductivity and drop of the Seebeck coefficient. The change of the conductivity type from positive to negative in the composition range x = 0 - 0.6 took place after cold pressing and composition dependencies of the properties became more complex. The maximum figure of merit value (Zmax = (3.1±0.4)·10-3 K-1) that was achieved in cold-pressed annealed samples at x = 0.8 was comparable to the values of Z for single crystals of undoped (Bi₁₋xSbx)₂Te₃ solid solutions and for polycrystalline samples produced by other methods. It follows from the data obtained that the proposed method of preparing the samples of (Bi₁₋xSbx)₂Te₃ solid solutions by cold pressing and subsequent annealing may appear to be useful in thermoelectric devices.